Design and development of measurement system for emergency depopulation of chicken farms during an avian influenza outbreak - Wong, Adam Teng How (2019)
The exercise of emergency depopulation of livestock using CO2 has been widely applied overseas and deem as a humane process. Such practice can be done either by placing livestock in a bag or a sealed environment followed by introducing CO2. This process requires a recommended level of CO2 concentration value of 45% or 450000ppm. However, the practices of introducing CO2 into a sealed barn/environment for culling hasn’t been tested in Singapore. Therefore, a study is required to check on the applicability of the method initiated by the Agri-Food & Veterinary Authority of Singapore (AVA). To evaluate the methodology, sensory measurement values are required. As the conventional sensor which is viable to the studies are commonly available for single point measurement. It does not give an actual physical representation of the dissipation of CO2 gas. Thus, to obtain a better representation multiple sensor are required in a different location. This will show a better real-time dissipation of the gas in the sealed barn. The device developed will be placed in different locations to take measurements such as CO2, O2 and temperature. Information collected will then be transmitted wirelessly back to a host’s PC to be viewed real time through a user interface and data logged for the studies.